Intelligent Vision System for Door Sensing Mobile Robot - Jharna Majumdar; R Praveen Kumar Jain; Venkatesh G M; Swaroop R (Institute of Advanced Engineering and Science, 2012)
Wheeled Mobile Robots find numerous applications in the Indoor man made structured environments. In order to operate effectively, the robots must be capable of sensing its surroundings. Computer Vision is one of the prime research areas directed towards achieving these sensing capabilities. In this paper, we present a Door Sensing Mobile Robot capable of navigating in the indoor environment. A robust and inexpensive approach for recognition and classification of the door, based on monocular vision system helps the mobile robot in decision making. To prove the efficacy of the algorithm we have designed and developed a ‘Differentially’ Driven Mobile Robot. A wall following behavior using Ultra Sonic range sensors is employed by the mobile robot for navigation in the corridors. Field Programmable Gate Arrays (FPGA) have been used for the implementation of PD Controller for wall following and PID Controller to control the speed of the Geared DC Motor.DOI: http://dx.doi.org/10.11591/ijra.v1i4.1262